Adaptive active fault-tolerant control of generic hypersonic flight vehicles. (February 2015) - Ji, Yuehui; Zhou, Hailiang; Zong, Qun
A theoretical framework of active fault-tolerant control is exploited for a hypersonic flight vehicle longitudinal dynamical system in cruise phase subject to actuator loss-of-effectiveness fault. First, an active fault detection scheme is proposed by designing a nonlinear fault detection observer for the faulty hypersonic flight vehicle model. A finite-time convergence fault-tolerant controller is proposed on the basis of combined back-stepping and sliding mode technology. Moreover, the adaptive law is developed to estimate the bound information of actuator efficiency factor. The fault-free controller is accomplished which guarantees the globally asymptotic output tracking and boundedness of the closed-loop system. Finally, numerical simulations in Simulation and Verification Platform are presented to illustrate that the proposed fault-tolerant control strategy is effective in providing satisfactory tracking performance and rejecting actuator faults in a climbing maneuver case.